Kraus' recreation and leisure in modern society - McLean, Daniel D.; Hurd, Amy R.; Anderson, Denise M. 1970- (Jones & Bartlett Learning, 2019)
Reorganized and streamline to enhance learning outcomes, the eleventh edition of Kraus' recreation and leisure in modern society provides a detailed introduction to the history, developments, and current trends in leisure studies. The eleventh edition focuses on the challenges and opportunities impacting the profession- including dramatic demographic changes and new technologies- through an array of pedagogical features, including engaging sidebars and case studies addressing contemporary issues. Focusing on the ten different types of organizations-raging from nonprofit community organizations and armed forces recreation to sports management and travel and tourism sponsors- the eleventh edition is an invaluable resource for students considering a career in the recreation and leisure industry